Math, asked by jakirhussain600076, 1 year ago

If a,b and c are in ap then prove that a(b+c)/bc, b(c+a)/ca and c(b+a)/ab

Answers

Answered by jitekumar4201
0

Answer:

Hence, \dfrac{a(b+c)}{bc} , \dfrac{b(c+a)}{ca} \ and \ \dfrac{c(b+a)}{ab} are in A.P.

Step-by-step explanation:

Given that-

a, b and c are in A.P. then-

b = \dfrac{a+c}{2}

2b = (a + c)    --------------- 1

\dfrac{a(b + c)}{bc} , \dfrac{b(c + a)}{ca} \ and \ \dfrac{c(b + a)}{ab} will be in AP if -

\dfrac{2b(c + a)}{ca} = \dfrac{a(b + c)}{bc}+\dfrac{c(a+b)}{ab}

L.H.S-

We have-

= \dfrac{2b(c+a)}{ca}

But a + c = 2b

= \dfrac{2b \times 2b}{ca}

L.H.S. = \dfrac{4b^{2} }{ca}

R.H.S = \dfrac{a(b+c)}{bc}+\dfrac{c(a+b)}{ab}

= \dfrac{ab+ac}{bc}+\dfrac{ac+bc}{ab}

= \dfrac{a(ab+ac)+c(ac+bc)}{abc}

= \dfrac{ab^{2}+a^{2}c+ac^{2}+bc^{2}}{abc}

= \dfrac{ac(a+c) + b(a^{2}+c^{2})}{abc}

= \dfrac{ac(2b) + b(a^{2}+c^{2}) }{abc}

= \dfrac{2abc + ba^{2}+bc^{2}}{abc}

= \dfrac{b(2ac + a^{2}+c^{2})  }{abc}

= \dfrac{a^{2}+c^{2}+2ac  }{ac}

But a^{2}+c^{2}+2ac = (a+c)^{2}

= \dfrac{(a+c)^{2} }{ac}

But  (a + c) = 2b

= \dfrac{(2b)^{2} }{ac}

= \dfrac{4b^{2}}{ac}

R.H.S = \dfrac{4b^{2}}{ac}

So, L.H.S. = R.H.S.

Hence, \dfrac{a(b+c)}{bc} , \dfrac{b(c+a)}{ca} \ and \ \dfrac{c(b+a)}{ab} are in A.P.

Similar questions